THE EFFECT OF CURRENT RATIO (CR) AND DEBT TO EQUITY RATIO (DER) ON RETURN ON ASSETS (ROA) IN PROPERTY AND REAL ESTATE SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) FOR THE PERIOD 2021-2025 - Lesti Mutia; Didin Rasyidin Wahyu; Ombi Romli (International Journal of Economy, Education and Entrepreneurship (IJE3), 2026)
Profitability is an important indicator for assessing a company's financial performance. Return on Assets (ROA) measures a company's ability to generate profits from its assets. This study analyzes the impact of the Current Ratio (CR) and Debt to Equity Ratio (DER) on ROA in property and real estate companies in Indonesia from 2021 to 2025. This study aims to find out the effect of the Current Ratio (CR) on Return on Assets (ROA), the effect of the Debt to Equity Ratio (DER) on Return on Assets (ROA), and the combined effect of CR and DER on ROA. This study uses a quantitative method and an associative approach. Secondary data were taken from the financial reports of property companies on the Indonesia Stock Exchange for the 2021–2025 period. Sampling was carried out using purposive sampling, and data analysis was carried out using multiple linear regression in SPSS. The research results show that the Current Ratio (CR) and Debt to Equity Ratio (DER) affect Return on Assets (ROA) in property and real estate sub-sector companies on the Indonesia Stock Exchange from 2021–2025. Based on the research results, it can be concluded that the Current Ratio (CR) and Debt to Equity Ratio (DER) are factors that influence Return on Assets (ROA). Therefore, companies need to maintain their liquidity levels and manage their capital structure optimally to boost profitability and support the company's financial performance.